Reducing Disparities in Postpartum Care Utilization: Development of a Clinical Risk Assessment Tool. (24th December 2022) - Tenfelde, Sandi; Joyce, Cara; Tell, Dina; Masinter, Lisa; Wallander‐ Gemkow, Jena; Garfield, Lindsey
Abstract : Introduction: Patients receiving care at Federally Qualified Health Centers (FQHCs) have low postpartum care attendance. Perinatal morbidity and mortality disproportionately affect patients with low‐income and are potentially preventable. The purpose of this study was to develop a clinical decision support tool to identify FQHC patients less likely to return for postpartum care. To accomplish this purpose, we evaluated established predictors and novel risk factors in our patient population. Methods: This is a retrospective, secondary data analysis of 50, 022 patients who received prenatal care past 24 weeks' gestation in FQHCs between 2012 and 2017. The postpartum visit was defined using Healthcare Effectiveness Data and Information Set measures as early care (birth to 21 days) and later care (21‐84 days). Anderson's Behavioral Model for Access to Healthcare guided inclusion of potentially predictive factors. We stratified data by postpartum care attendance, and a final predictive model was selected by model fit statistics and clinical relevance. Results: In our sample, 64% of birthing persons attended postpartum care at FQHCs. Of those who returned for care, 38% returned within 21 days postbirth and 62% returned between 21 and 84 days, with 28% returning for both early and later care. Predictors for postpartum care attendance included maternal age, parity, gestational age at first visit, and number of prenatal care visits. A clinical decision support tool for identifying patients less likely to return for care was created. Discussion: An easy to implement clinical decision support tool can help identify FQHC patients at risk for postpartum nonattendance. Future interventions to improve adequacy of prenatal care can encourage early entry into prenatal care and sufficient prenatal visits. These efforts may improve postpartum care attendance and maternal health.